Diagnostic imaging of hypertrophic pyloric stenosis (HPS) - Frković, Marija (Radiology and oncology (Ljubljana), 2001)
Imaging of the abdomen in children with suspected hypertrophic pyloric stenosis has been traditionally performed by plain film radiography and upper gastrointestinal contrast studies. In many clinical situations, this approach has been modified or replaced by ultrasound examination. The authors aimed to analyse the value of diagnostic algorithm in children with hypertrophic pyloric stenosis confirmed at surgery in our hospital. Patients and methods. The authors made a five year retrospective review of hospital records of all children operated on for HPS in Clinical Hospital Centre Zagreb-Rebro and found out that 14 boys, between 2 (17 days) and 10 weeks of life (75 days) underwent surgery due to HPS. Results. Specific radiographic signs were: string sign, double track sign, elongation and narrowing of pyloric, canal, mushroom sign, gastric distension with fluid and beak sign. Ultrasound was performed in 9 patients, one of them was false negative (sonographer admitted that he had no experience), the rest were positive. Conclusions. If the physical examination is negative or equivocal, sonography by an experienced sonographer must be performed. If the ultrasound finding is negative, than theinfant should undergo to barium upper gastrointestinal studies (UGI). If HPS is not a primary diagnostic question, it is better to perform UGI first inorder to make a correct diagnosis.
Keywords: Barium radioisotopes; Child; Contrast media; Hypertrophy; Pyloric stenosis; Radiography; radiološka diagnostika; Radionuclide imaging; trebuh; Ultrasonography; ultrazvočna diagnostika; želodec